RETRACTED: In-Stent Thrombosis in the Middle Cerebral Artery (MCA): A Case Report - Xian-jun, Zhang; Hai-feng, Li; Yong, Zhang; Hong, Li; Zong-chao, Liu (Journal of Neurological Research And Therapy, 2015)
This article has been retracted on November 20, 2015. VIEW THE RETRACTION NOTICE (https://doi.org/10.14302/issn.2470-5020.jnrt-25-5846) In-stent thrombosis (IST) is a complication of angioplasty and stenting, especially in the vessels with smaller diameter. We present a case of subacute IST after stenting treatment of an isolated higher stenosis of the right middle cerebral artery (MCA). Analysis of clinical features and emergent brain image helped to indicate the pathophysiological mechanism underlining the symptoms of this patient. Emergent Transcranial Doppler (TCD) helped to evaluate the compensatory collateral circulation and provided good supporting evidence in deducing the mechanism of IST. Slightly larger size of the implanted stent that caused dissection or vascular endothelium injury was presumed in this patient. Persistent evidence of inflammatory factors might also contribute to IST in this patient.
Keywords: middle cerebral artery; intracranial stenosis; angioplasty; in-stent thrombosis; middle cerebral artery; intracranial stenosis; angioplasty; in-stent thrombosis